Back to the metal age: battle for metals at the host–pathogen interface during urinary tract infection - Subashchandrabose, Sargurunathan (Metallomics, 2015)
Urinary tract infection (UTI) represents one of the most common bacterial infections in humans and uropathogenic E. coli (UPEC) is the major causative agent of UTI in people. Research on UPEC and other bacterial pathogens causing UTI has now identified the critical role of metal transport systems in the pathogenesis of UTI. Here we review the major effectors of metal transport in bacteria and host proteins that impair metal acquisition by bacterial pathogens. In particular, we describe the studies that identified iron, zinc and nickel import and copper export as key virulence and fitness determinants during UTI. Various metal transport systems and mechanisms that govern the expression of metal transport systems are also presented here. Specific examples from UPEC and other uropathogens, when available, are presented to depict the battle for metals at the host–pathogen interface during UTI.